THE ASSESSMENT OF PATIENTS WITH NON-EROSIVE GASTROESOPHAGEAL REFLUX DISEASE BY USING THE BRAVO® PH MONITORING SYSTEM - Gok, Mehmet; Gencdal, Genco (Sanamed, 2022)
Background and aim: Gastroesophageal reflux disease (GERD) is a common disease in the world. GERD is always treated with drugs. The Bravo® wireless pH monitoring system is a good technique. The Bravo® may affect increasing the specificity and sensitivity in the diagnosis of GERD with its 48-hour recording feature.  In this study, we aimed to assess the diagnostic performance of the Bravo® pH monitoring system in patients with non-erosive GERD.Materials and Methods: Patients with non-erosive reflux disease (normal endoscopy) whose symptoms persisted after PPI treatment (at least two months) were included in the study. All patients had upper gastrointestinal system endoscopies performed in our clinic between January 2013 and December 2019. All patients had a 48-hour Bravo® wireless pH monitoring record.Results: Twenty-three patients (M: 18 (78.3%; Age:35.7±11) were included in the study. All patients completed the 2-day recording protocol. During and after the procedure, no patient showed any adverse effects of the Bravo® procedure. We diagnosed GERD in 13 of 23 patients by Bravo® capsule. According to the Bravo® pH-meter recordings; Total time pH
Keywords: Gastroesophageal Reflux; Esophagus; reflux